PENGARUH KECERDASAN EMOSIONAL, FASILITAS KERJA DAN PENGEMBANGAN SUMBER DAYA MANUSIA TERHADAP PRODUKTIVITAS KERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada Karyawan Pt. Tri Bakti Sarimas Pekanbaru) - Ricky Gunawan; Marnis '; Ahmad Rifqi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to analyze the influence of Emotional Intelligence, Working Facilities and Human Resources Development of the Work Productivity with job satisfaction as an intervening variable in PT. Tri Bakti Sarimas Pekanbaru. In this study there were five variable, Emotional Intelligence (X1), Work Facilities (X2), Human Resources Development (X3), job satisfaction (Y1), and Work Productivity (Y2). Population of this study were all employees of PT. Tri Bakti Sarimas Pekanbaru with a sample of 122 respondents were selected using census method. Collecting data in this study is done by giving questionnaires to the respondents. In terms of data analysis, this study using Path Analysis with SPSS version 21. The results of this study showed that the variables Emotional Intelligence, Working Facilities and Human Resources Development directly influence job satisfaction then Emotional Intelligence and Human Resource Development influence directly to the Work Productivity, while variable Work Facilities not directly affect Work Productivity and Job Satisfaction also affects the Work Productivity. Then the variable job satisfaction mediates the relationship variables Emotional Intelligence, Working Facilities and Human Resources Development of the Work Productivity.Keyword : Emotional Intelligence, Working Facilities, Human Resources Development, Job Satisfaction, and Work Productivity